Changes in women's use of illicit drugs following imprisonment. - Plugge, E; Yudkin, P; Douglas, N (2009)
AIM: To provide data on changes in illegal drug use in women following imprisonment. DESIGN: Prospective cohort study. SETTING: Recruitment took place in two prisons in the Midlands and South-East England and follow-up in 13 prisons across England. PARTICIPANTS: A total of 505 women prisoners participated, a response rate of 82%. Measurements Questions about drug use were contained within a questionnaire which examined broad aspects of health. On entry into prison, women answered questions about daily drug use and injecting drug use prior to imprisonment. One month later the questionnaires examined drug use during this period of imprisonment. FINDINGS: Prior to imprisonment, 53% [95% confidence interval (CI): 49-58%] of women took at least one illegal drug daily and 38% (CI: 34-42%) said they had ever injected drugs. Following imprisonment, some women continued to use drugs; 14% (CI: 10-20%) of women reported using at least one illegal drug daily and 2% (CI: 0.7-5%) of women had injected drugs. There were important changes in the types of drugs used; there was a change in use from crack and heroin to benzodiazepines and opiate substitutes. Prior to imprisonment, women most commonly used crack and heroin, but in prison the two most commonly used illegal drugs were benzodiazepines and opiate substitutes. CONCLUSIONS: The study provides quantitative evidence of the impact of imprisonment on drug use among women. It highlights the need for enhanced drug treatment services and stronger measures to reduce the availability of illegal drugs to women in prison.